Recent developments in laser scanning :Powerpoint - Kraak, M.J. (University of Twente, 2020)
This lecture presents: Overview of developments in laser scanning; Developments in hardware technology: Multiple Pulses in the Air (MPiA); Full-waveform recording; More versatile terrestrial laser scanners; Developments in SLAM; Honorable mention: Kinect; Developments in processing methodology and applications: Rail track detection and modelling.